Phaco-antigenic glaucoma following uncomplicated cataract surgery. Issue 1 (July 2019) - Chiu, Alexander Kin Chiang; Mathews, Divya
Introduction: Phaco-antigenic glaucoma occurs in less than 1% of cataract surgeries. Managing this rare complication is challenging, especially when there are few documented cases reported. We describe the challenges of managing a case of bilateral phaco-antigenic glaucoma following uncomplicated cataract surgery requiring viscocanalostomy. Case description: An 82-year-old atopic lady presented with a 2-day history of painful injected right eye. She was 4 days post left and 8 days post right uncomplicated cataract surgery. On examination, the anterior chambers were deep with no hypopyon. Intraocular pressure was raised at 38 mmHg in the right eye and 24 mmHg in the left eye initially. However, intraocular pressure remained uncontrolled despite maximum medical treatment; she attended A + E six times within 11 days with intraocular pressures of up to 48 mmHg in the right eye and 46 mmHg in the left eye. A vitreous biopsy was reported negative for infective organisms. Eventually, bilateral viscocanalostomies were performed and vision improved to 0.24 logMAR in both eyes with intraocular pressures of 8 mmHg in the right eye and 10 mmHg in the left eye. Conclusion: We present a rare presentation of phaco-antigenic glaucoma following an uncomplicated cataract surgical procedure with good results following timely intervention.